p89c-Myb is not required for fetal or adult hematopoiesis - Baker, Stacey J. (2010)
The c-myb gene encodes two proteins, termed p75 and p89. Of these, the larger isoform is transcribed from an alternatively spliced message that contains an additional exon, exon 9A. Disruption of the c-myb locus in mice results in embryonic lethality due to defective hematopoiesis and in the adult, tissue-specific inactivation of c-myb in hematopoietic tissues blocks differentiation along several lineages. The c-myb knock-out mouse models described thus far result in the disruption of both the p75 and p89 isoforms, making it impossible to assign a definitive role to p89(c-Myb) in development and hematopoiesis. We have therefore generated a null-mutant mouse where exon 9A has been systemically deleted that results in the absence of only the p89-myb transcript and protein. Unlike disruption of both forms of the c-myb gene, loss of only the p89-encoding isoform does not have any deleterious effects on mammalian hematopoiesis and development.